1927 Mass. Acts 416 - (:unkn) unknown (My University, 1927)
An Act Relative to Machine Guns and Other Firearms, ch. 326, § 5: Prohibited the carrying of a pistol, revolver, machine gun, stiletto, dagger, dirk knife, slungshot, metallic knuckles, or sawed off shotgun, billy, or dangerous weapon if arrested upon a warrant for an alleged crime. Punishable by imprisonment of 6 months to 2.5 years.
Keywords: CARRY - DANGEROUS PERSONS